COVID-19: REFLEXÕES SOBRE SEUS IMPACTOS NA QUALIDADE DO AR E NAS MODIFICAÇÕES CLIMÁTICAS - Ribeiro, José Claudio Junqueira; Custódio, Maraluce Maria; Praça, Diego Henrique Pereira (Veredas do Direito, 2021)
The atmosphere is one of the elements of the natural environment and its protection has been sought in recent times because, it is the environment that is very impacted and that has repercussions on human life, due to the worsening of air quality and climate changes. In this sense, the importance of the atmospheric environment as an essential element in life is highlighted in this work and the impacts that the SARS-CoV-2 virus, dissipated by the air and that started the current Covid 19™s pandemic. If so far the concerns environmental in relation to air had been guided by physical, chemical or physical-chemical changes, the COVID-19 pandemic brought to light the need to be concerned with biological changes. This article focuses the causes and effects of global warming and air pollution, indicating how the COVID-19 pandemic has positively and negatively related to these environmental problems. The methodology adopted was the hypothetical deductive, with a qualitative research approach based on publications, articles, document analyzes and official data dissemination sites. With a theoretical framework, Taylor's theory (1981) of the need to create moral principles for the relationship of human beings with the natural environment. Finally, to conclude that it is necessary to re-discuss the relationship between human beings and the natural world, with the imposition of new moral principles that can prevent future epidemics and reduce climatic effects.